One man (phōs) in heaven: Adam-Moses polemics in the Romanian versions of "The Testament of Abraham" and Ezekiel the Tragedian's "Exagoge" - Bunta, Silviu Nicolae (Journal for the study of the pseudepigrapha, 2007)
Several scholars have noted that already in the Second Temple period Judaism developed speculations that associated Adam with the primordial light. The present study explores two possible expressions of such speculations, namely, a Romanian version of the "Testament of Abraham" and Ezekiel the Tragedian's "Exagoge". A Romanian manuscript tradition of the testament, diverging from the Greek versions, portrays Adam as a "luminous man". A second manuscript tradition makes reference to Adam's face in terms reminiscent of Moses' luminous face on Sinai. It is subsequently argued that the two phrases are expressions of early polemics between traditions about Adam's luminescence and traditions about a luminous Moses and that, on the side of Moses traditions, Ezekiel the Tragedian's "Exagoge" attests to a Mosaic claim over a prominent title in Adam-light speculations, namely, phōs.